The Image of The Hero in J.M. Synge’s Play The Playboy of the Western World (المجلة الدولية للبحوث العلمية, 2024)
This study will try to show that John Millington Synge (1871-1909) blended metaphysics, mythology and reality to produce an image of the ideal type of individual needed as the savior of Ireland, in particular, and mankind, in general.The hero concept is best understood as a rather curious and obsessional example of a spiritual phenomenon that reached something of a climax in the nineteenth century, most notably is the thought of Hegel, Ludwig Feuerbach, Thomas Carlyle, August Comte, Marx, and Nietzsche, namely, the uneasy substitution of purely secular objects of veneration for the traditional transcendental ones. Worship of God gave way to worship of man and human society – man as individual in capitalism and society in Marxism. This albeit gave rise to leaders like Hitler, Mussolini and all third world leaders in the first half of the 20th century.The playboy draws on the myth of the dying god or king who renews his life for the benefit of the community. In addition, in his preface to Playboy, Synge places himself in the mainstream of realism: "It is possible for a writer to be rich and copious in his words and at the same time to give the reality, which is the root of all poetry, to a comprehensive and natural form", thus he blends mythology and reality.As for metaphysics, Synge's definition of the literary qualities, or nature, of drama is extremely wide. He says, for example, "Art is but expression" (Works, II, 95). And the problem of the artist is that he feels "the inexpressible … We have walked with God" (Ibid).